Implementasi Prinsip Ekowisata pada Pengembangan Tradisi Kirab Tirta Amerta Sari di Desa Wisata Toyomarto Kecamatan Singosari Kabupaten Malang - Nabiilah Mahdiyah Farcha; Petir Pudjantoro (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Toyomarto Village is a tourist village in Malang Regency with the concept of ecotourism. Toyomarto Village has an interesting culture to visit, namely the Kirab Tirta Amerta Sari. Kirab Tirta Amerta Sari tradition is a water source ‘selametan’ which is part of the village alms, which is held once a year in the month of ‘Suro’. To maintain the resilience of the tradition, it is necessary to develop a tradition based on the principles of ecotourism. This research was conducted to find out the implementation of ecotourism principles in the development of the Kirab Tirta Amerta Sari Tradition, development steps and the impact of ecotourism on the development of the Kirab Tirta Amerta Sari Tradition. The research used a qualitative method of case study approach by collecting data through observation, interviews, and documentation. Data analysis used Miles and Huberman’s theory through the stages of data reduction, data presentation, and conclusion drawing. Based on the field result obtained, it is shown that the implementation of ecotourism principles in the development of the Kirab Tirta Amerta Sari Tradition in Toyomarto Village, because the development of kirab has been conceptualised by the community, so that activities can provide benefits and positive impact for local communities and visitors. There are two development steps to developing the kirab, namely educational development and promotion strategies, and the impacts included the formation of social cohesion, the preservation of culture and the environment, and the development of the local economy.